2023
DOI: 10.1161/strokeaha.123.040806
|View full text |Cite
|
Sign up to set email alerts
|

Role of Brain Imaging in the Prediction of Intracerebral Hemorrhage Following Endovascular Therapy for Acute Stroke

Abstract: Currently most acute ischemic stroke patients presenting with a large vessel occlusion are treated with endovascular therapy (EVT), which results in high rates of successful recanalization. Despite this success, more than half of EVT-treated patients are significantly disabled 3 months later partly due to the occurrence of post-EVT intracerebral hemorrhage. Predicting post-EVT intracerebral hemorrhage is important for individualizing treatment strategies in clinical practice (eg, safe initiation of early antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…This discrepancy may stem from the inclusion of patients in our study with large infarct cores in the anterior circulation and an ASPECTS score of ≤5, whereas previous EVT studies have largely excluded patients who had large infarct cores already present at the time of preoperative imaging. Several studies have demonstrated an association between larger cores on imaging and an increased risk of sICH after EVT ( 14 , 15 ). In most studies, an ASPECTS score of ≤5 was reported to be associated with an approximately 2-fold risk of ICH ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may stem from the inclusion of patients in our study with large infarct cores in the anterior circulation and an ASPECTS score of ≤5, whereas previous EVT studies have largely excluded patients who had large infarct cores already present at the time of preoperative imaging. Several studies have demonstrated an association between larger cores on imaging and an increased risk of sICH after EVT ( 14 , 15 ). In most studies, an ASPECTS score of ≤5 was reported to be associated with an approximately 2-fold risk of ICH ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also raise the possibility that the reason may lie in the definition we use for sICH, as previously mentioned by a recent article [28]. On the one hand, this definition does not consider the causal F I G U R E 3 Shift analysis of the modified Rankin Scale score at 3 months of follow-up according to asymptomatic parenchymal haemorrhage type 1 (aPH1).…”
Section: Discussionmentioning
confidence: 97%